Studi Kelayakam Pembangkit Tenaga Listrik Mikrohidro Desa Muara Urie Kecamatam Hampang Kabupaten Kotabaru KALSEL - Arief Budiyanto (Universitas Janabadra, 2016)
Kota Baru District has many small river which has the potential to be converted into electrical energy. The objective of the project is to provide the village Haulan river MuraUrie Hampang Kota Baru with a reliable, green, clean and economically viable source of electrical energy. This research has been conducted to assess the potential of hydropower and to design very low head water hydropower plant. The observational step started by measuring head and flow rate. Designing of water turbine should be considered the power available. Since the turbine usually run at low speed and the generator speed is quite high (1500 rpm), it requires speed increaser. Based on the primary data, the electrical power can be generated up to 30 kW. The implementation of the project will take approximately eight to ten months including the finalisation of the preparatory work (detailed design, tendering, contract awarding), actual implementation of the project, testing, commissioning and training of operators. Two villagers will be assigned and trained as operators for the operation and maintenance of the plant, in order to optimize the viability of the water source office of Kota Baru.